Children perception of parental empathy in relation with children empathy - Richaud, Maria Cristina (2013)
The aim of this paper is to study the development of empathy in middle and late childhood, and its origins, in part, in primary interpersonal relationships, especially with parents. Regarding this subject we are interested in analyzing whether children perception of parental empathy as a result of parental modelling can predict empathy in the child. Empathy is the ability to participate in the feelings or ideas of others, to feel sad about their unhappiness and good about their joy. In order to develop empathy, a child must be able to feel attachment to another person and must care if that person is hurting. The development of empathy and of the corresponding guilt and shame when one harms or fails to help another person, guarantees pro-social behaviour and altruism, even and preferably in the absence of external rewards and punishments. Empathy includes cognitive processes and emotional experiences, and implies a mainly cognitive response showing understanding of how another person feels as well as an emotional communion (Gallo, 1989). Haynes and Avery (1979) described empathy ?as the ability to recognize and understand another persons perceptions and feelings and to carefully express that understanding in an accepting response? (p. 527). The response may be either verbal or non-verbal, or pro-social behaviour such as sharing or helping. On the one hand, empathy can be defined cognitively in relation to perspective taking or understanding others.